Pendidikan, Kesehatan, dan Kemiskinan: (Studi tentang Efek Pendidikan terhadap Kesehatan dan Kemiskinan di Indonesia) - Juhaidi, Ahmad; Rafiah; Afifah, Annida; Hasanah, Putri Maulida (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
This study aimed to determine the effect of education level on the quality of public health and the poverty rate in Indonesia. We collected data from the Central Statistics Agency Republic of Indonesia (BPS RI) publications in 2020, 2021, and 2022. The districts sampled were 22 out of 416 districts/cities in Indonesia. In this study, the expected years of schooling indicate the level of education, health in terms of Life Expectancy Rate, and poverty using the percentage of poor people. With SPSS version 27, we conducted our analysis using descriptive statistics and linear regression. This study's findings show that education level affects health with a termination coefficient (R-Square) of 0.143 (14.3%). Other findings prove that the level of education affects the decline in the percentage of poor people in Indonesia. The contribution of the education level factor or the coefficient of termination (R-Square) is 0.18 (18%). This finding shows that other factors influence the reduction of poverty rates in Indonesia. This research makes valuable theoretical and practical contributions to education development in Indonesia.